2019
DOI: 10.4103/aca.aca_124_18
|View full text |Cite
|
Sign up to set email alerts
|

Proximal penholding method – A variant to enhance safety of ultrasoundguided central venous cannulation: A prospective pilot study

Abstract: Aims:A significant incidence of Posterior Vessel Wall Puncture (PVWP) was reported during ultrasound guidance (USG) for internal jugular vein (IJV) catheterization. We studied a new technique of USGIJV cannulation to minimize or avoid PVWP, thereby decreasing overall complication rate, irrespective of the operators' experience level.Materials and Methods:After ethical approval, a prospective study was conducted on adult patients of either gender between 18–65 years of age, belonging to the American Society of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…described the novel technique of the pen holding method. [ 4 ] The authors suggested that holding the needle on the hub like a pen allows better control enabling precise movement, thereby avoiding overshooting of the needle and posterior wall puncture. Also, holding the needle like a pen is more familiar to the hand and helps estimate the skin thickness and texture and accurately estimate the pressure required for the puncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…described the novel technique of the pen holding method. [ 4 ] The authors suggested that holding the needle on the hub like a pen allows better control enabling precise movement, thereby avoiding overshooting of the needle and posterior wall puncture. Also, holding the needle like a pen is more familiar to the hand and helps estimate the skin thickness and texture and accurately estimate the pressure required for the puncture.…”
Section: Discussionmentioning
confidence: 99%
“…One of the techniques to avoid PVWP is the ‘proximal pen holding method’ of needle holding. [ 4 ] This study was aimed to compare the pen holding method of needle holding with the conventional needle holding technique for real-time USG-guided IJV catheterisation in short axis (SAX) view. The study’s primary objective was to compare the incidence of posterior vessel wall puncture between both the techniques.…”
Section: Introductionmentioning
confidence: 99%